Pengaruh Kecerdasan Emosional Terhadap Kinerja Pegawai Perguruan Tinggi La Tansa Mashiro Di Rangkasbitung - Soleh Rosyad; M. Zaenal Arifin; Eris Harismasakti (E-Journal Studia Manajemen, 2014)
The purpose of this research was to examine empirically the effect between emotional intelligence on job performance among the employees at La Tansa Mashiro Higher Education in Rangkasbitung. The subjects of this research were 76 employees selected as samples by using total sampling technique taken from the overall population of 76 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ job performance was positively affected by the emotional intelligence in La Tansa Mashiro Higher Education in Rangkasbitung. The findings suggest that the variation of the job performance of the employees might have been affected by emotional intelligence.